Protease Production from UV Mutated Bacillus subtilis (Bangladesh Journal of Scientific and Industrial Research, 2012)
UV mutation of the strain has significant contributation to enhance the yield of protease enzyme from Bacillus subtilis bacteria under the  cultivation conditions in submerged fermentation. The fermentation medium used for the production of protease composed of carbon  sources 1%, organic 1% or inorganic nitrogen sources 0.5% , K2HPO4 0.2 %, CaCl2 0.04% and MgSO4 0.02 % by mutated Bacillus subtilis  G-4 under the optimum parameters which are important to induce the mutated strain to produce high units of the protease, which were  temperature 37.5°C, pH 9, inoculum size 3 % v/v, glucose 1% as carbon source and peptone 1% as nitrogen source were give the maximum  455.25 + 1.66 units of protease. The results of stability studies revealed that protease of B. subtilis G-4 was stable over a broad range  of temperature (30 to 60°C) and pH (8 to 12). However, maximum activity (155.45U/ml) was observed at temperature 50°C and pH 10.  These characteristics render its potential use in detergent industries for detergent formulation.DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10725 Bangladesh J. Sci. Ind. Res. 47(1), 69-76, 2012